Work Attachment as Intervening Transformational Leadership and Work-Life Balance to Intention to Stay in Millennial Generation in Automotive Company - Fitri Rezeki (Universitas Pendidikan Ganesha, 2023)
Generational Change has given many colors to the world of work and organizations/companies. Human Resources is a department that must be responsive and critically creative in responding to change. This research focuses on analyze alternative ways to maintain millennials in companies in terms of transformational leadership, work life balance, and career development as millennials hope to bond and stay. The sample was 232 out of a total population of 281. Data processing is using Smart PLS 3. The result found transformational leadership has a significant positive effect on work attachment, value 0.024; P-Value is 0.013, and Leaders are already forward-oriented at 62.07%. Work life balance has a significant positive effect on work attachment, value 0.536. P-Value and work life balance have been met by 66.81%. Indirectly, through work attachment transformational leadership affects the intention to stay positive significant value 0.134 and P-Value (0.034). Work life balance affects intention to stay through positive work attachment significant value 0.322 and P-Value 0.000. Another interesting result is that 87.93% of employees are comfortable, 50% of employees are until retirement, and 48.71% of employees will last >15 years.